CD8+ T cell programming by cytomegalovirus vectors: applications in prophylactic and therapeutic vaccination. (August 2017) - Früh, Klaus; Picker, Louis
Highlights: Effector memory T cell (TEM ) inducing vaccines represent a novel paradigm in vaccine development that enables the early intercept of incoming or reactivating pathogens. Cytomegalovirus (CMV)-based vectors elicit and maintain high frequency TEM to inserted antigens. Rhesus CMV-based vaccines control and clear highly pathogenic simian immunodeficiency virus (SIV). Specific deletions in the RhCMV genome permit the programming of CD8+ T cells to four different, non-overlapping sets of epitopes restricted by MHC-I, MHC-II or MHC-E molecules. CMV-based vaccines can be designed to elicit CD8+ T cell responses that exploit any given pathogen's immunologic vulnerability and thereby provide optimal protection. Abstract : Vectors based on cytomegalovirus (CMV) represent a novel vaccine platform that maintains high frequencies of non-exhausted effector memory T cells in both CMV sero-positive and sero-negative individuals. In non-human primate models, CMV vectored vaccines provide unprecedented protection against simian immunodeficiency virus (SIV). Moreover, CMV vectors can be genetically altered to program highly diverse CD8+ T cell responses that differ in their epitope targeting including conventional, MHC-I restricted CD8+ T cells as well as unconventional CD8+ T cells restricted by MHC class II or non-polymorphic MHC-E. By modifying cytomegaloviral determinants that control unconventional T cell priming it is possible to uniquely tailor the CD8+ T cell response for each individual disease target in order to maximize prophylactic or therapeutic protection.